2009
DOI: 10.1002/app.30342
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the production of high solids acrylic/methacrylic core‐shell latices

Abstract: Well-defined poly(butyl acrylate)/poly(methyl methacrylate) (PBA/PMMA) core shell particles with a moderately high solid content (49%) and particle diameters of less than 200 nm were prepared via seeded emulsion polymerization with a redox initiator and an anionic surfactant. Lowviscosity (less than 150 cps at 20 s À1) latex products were obtained by controlling the particle size distribution to within certain limits. Polymerization conversion and kinetics were followed gravimetrically and were adjusted so as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The pH was measured and found to have a value of 7, all the prepared latexes remained stable with respect to coagulation for more than six months, similar to other high solid content latexes reported in the literature. 25,26 The hydrodynamic radius, R h of the latex particles was measured by dynamic light scattering 27 (DLS) and found to vary with both the surfactant type and the surfactant content (monomer-to-surfactant molar ratio, S) as shown in Table 2. For each surfactant, it is observed that the R h of the latex particles decreases with increasing surfactant content, as indicated by the decreasing monomer-to-surfactant molar ratio fed into the reaction mixture.…”
Section: Latex Propertiesmentioning
confidence: 99%
“…The pH was measured and found to have a value of 7, all the prepared latexes remained stable with respect to coagulation for more than six months, similar to other high solid content latexes reported in the literature. 25,26 The hydrodynamic radius, R h of the latex particles was measured by dynamic light scattering 27 (DLS) and found to vary with both the surfactant type and the surfactant content (monomer-to-surfactant molar ratio, S) as shown in Table 2. For each surfactant, it is observed that the R h of the latex particles decreases with increasing surfactant content, as indicated by the decreasing monomer-to-surfactant molar ratio fed into the reaction mixture.…”
Section: Latex Propertiesmentioning
confidence: 99%
“…For example, Moghbeli and Tolue synthesized PBA‐PMMA core–shell particles with average diameters from 100 to 170 nm via two‐stage seeded emulsion polymerization for the purpose of being used as a modifier of particulate flow and toughening of polyvinyl chloride. Udagama and Mckenna prepared PBA‐PMMA core–shell particles with diameters around 200 nm via seeded emulsion polymerization for the purpose of obtaining low‐viscosity and high solid content latex products. However, no information was provided regarding the transparency and the anti‐crease‐whitening property.…”
Section: Introductionmentioning
confidence: 99%
“…However, microemulsion polymerization has the disadvantage that typically requires large amount of surfactants yielding low polymer content. Nevertheless, it has been shown that latexes of polystyrene (PSt), poly(butyl acrylate) (PBA), and other acrylic or vinyl polymers can be produced with high solid content ( > 30 wt%) using smaller amounts of surfactant by semicontinuous microemulsion polymerization, without altering the basic features of the microemulsion‐made polymer nanoparticles [34–39]. Using this approach, our group has been able to synthesize PBA/PST (or PSt/PBA) core/shell polymer latexes by semicontinuous two‐stage polymerization with high‐polymer content and showed that the size of the core/shell particles and the position of the soft and hard polymers (core or shell) affect dramatically the mechanical properties of these materials [32, 33, 40].…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, our group has been able to synthesize PBA/PST (or PSt/PBA) core/shell polymer latexes by semicontinuous two‐stage polymerization with high‐polymer content and showed that the size of the core/shell particles and the position of the soft and hard polymers (core or shell) affect dramatically the mechanical properties of these materials [32, 33, 40]. Udagama and Mckenna [35] reported high solid content latexes (49 wt%) containing well‐defined PBA/PMMA core/shell particles with diameters smaller than 200 nm prepared via seeded emulsion polymerization. Recently, Liu et al [41] reported using a functionalized monomer, IA, the modification of the properties of PBA/poly(methyl methacrylate‐ co ‐itaconic acid) core/shell nanoparticles of 50–65 nm, by a seeded emulsion polymerization, but no mechanical properties were reported.…”
Section: Introductionmentioning
confidence: 99%